Sobre tranchets do Bronze Final do Ocidente Peninsular - Vilaça, Raquel (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
In 1976, Philine Kalb drew attention to three bronze artefacts from central Portugal. She interpreted these correctly as tranchets, and pointed out a typological detail of the haft area, namely the spaces on the tangs, as found in Huelva-type swords. The present study deals with these tools again, now on the basis of about twenty pieces of the same type, all from the western Iberian Peninsula, some unpublished. Descriptive and typological analyses of each piece are followed by discussion of the main differences; reference is made to results of the metallurgical analyses of some of the pieces. The contexts of the tranchets are discussed. The use of these tools has aroused some controversy; the author follows Kalb’s theory that they were knives for cutting hides.